GENDER ASPECT OF NEGOTIATIONS IN THE SPORTS SECTOR AS A FACTOR IN ENSURING EQUAL OPPORTUNITIES (World Conference on Social Sciences, Law and Public Policy, 2026)
The article examines the impact of gender determinants on the negotiation process within the professional sports industry. The author analyzes how specific negotiation styles and prevailing gender stereotypes shape athletes’ and sports officials’ access to resources and career opportunities. The paper substantiates the thesis that the institutionalization of a gender-oriented approach in sports law is a necessary condition for overcoming structural inequality.
Keywords: gender equality in sport, sports management, negotiation strategies, inclusivity, negotiations.